Treatment Outcomes of Patients with Squamous Cell Carcinoma of the Vulva: The Largest Series from a Tertiary Care Hospital. (3rd September 2018) - Meelapkij, Panida; Suprasert, Prapaporn; Baisai, Orthai
Abstract : Objective . To evaluate the outcomes of squamous cell carcinoma (SCCA) of the vulva treated at our tertiary care center. Methods . The medical records of SCCA patients treated between January 2006 and December 2015 were retrospectively reviewed. Results . One hundred forty-five patients met the criteria with the median age of 57 years old, and 58.6% had an underlying disease. The distribution of stages was as follows: IA 6.2%, IB 21.4%, II 26.2%, IIIA 14.5%, IIIB 6.2%, IIIC 9.7%, IVA 9.0%, and IVB 6.9%. One hundred and nine patients underwent surgical intervention and radical local excision with bilateral groin node dissection as the most frequent procedure. Approximately half of the patients received combined treatment with surgery followed by radiation with or without chemotherapy. Recurrence developed in 127 patients after the median follow-up time of one year with the common sites in the groin and vulva region. However, no significant difference in survival occurred in patients with and without groin node recurrence (15 vs. 28 months, P = 0.109 ). The five-year overall survival was 50.8%. Conclusions . The survival of patients with SCCA vulvar cancer was modest. The common failure sites were groin and vulva regions with unfavorable outcomes.